2019
DOI: 10.3389/fvets.2019.00345
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Diffusion Tensor Magnetic Resonance Tractography of the Sheep Brain: An Atlas of the Ovine White Matter Fiber Bundles

Abstract: Diffusion Tensor Magnetic Resonance Imaging (DTI) allows to decode the mobility of water molecules in cerebral tissue, which is highly directional along myelinated fibers. By integrating the direction of highest water diffusion through the tissue, DTI Tractography enables a non-invasive dissection of brain fiber bundles. As such, this technique is a unique probe for in vivo characterization of white matter architecture. Unraveling the principal brain texture features of preclinical models that are advantageous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…The WM matrix is composed of aligned myelinated axons and relatively soft extracellular matrix [45]. In the case of S∥, the cross sectional area of the tissue exposed to infusate pressure is composed of both axons and the relatively soft ECM, whereas in case of S⊥, the exposed cross-sectional area is predominantly composed of axons [39]. It is harder to deform axons (stiffness of a single axon reported to be e.g.…”
Section: A Effect Of Directionality Of Axons On Hydraulic Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The WM matrix is composed of aligned myelinated axons and relatively soft extracellular matrix [45]. In the case of S∥, the cross sectional area of the tissue exposed to infusate pressure is composed of both axons and the relatively soft ECM, whereas in case of S⊥, the exposed cross-sectional area is predominantly composed of axons [39]. It is harder to deform axons (stiffness of a single axon reported to be e.g.…”
Section: A Effect Of Directionality Of Axons On Hydraulic Permeabilitymentioning
confidence: 99%
“…WM anisotropy, due to directionality of axons in the matrix [38], [39], makes WM hydraulic permeability directiondependent. This detail is often overlooked, and only a few theoretical studies have reported the effect of anisotropy of brain WM on the hydraulic permeability [40].…”
Section: Introductionmentioning
confidence: 99%
“…As DTI tractography assesses the structural integrity of white matter, it has been widely used for prognostic and/or diagnostic purposes in various brain pathologies such as stroke (3)(4)(5)(6), neurodegenerative diseases (7)(8)(9)(10)(11), and brain tumors (12). With the increasing availability of high-field-strength MRI (1.5 and 3 T) in veterinary facilities (13)(14)(15)(16)(17), the use of this technique is now gradually growing for the description of white matter anatomy and structural connectivity of domestic mammals (dog, cat, ferret, and sheep) (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). These collected anatomical data are of particular interest as they might have applications in both veterinary medicine and experimental research.…”
Section: Introductionmentioning
confidence: 99%
“…In order to study sexual behaviour and hormonal status in the sheep brain, functional magnetic resonance imaging (fMRI) demonstrated valuable features (Ella et al, 2019). Recently, a few studies explored MRI functional possibilities in the sheep brain (Lee et al, 2015;Pieri et al, 2019) demonstrating reproducible and translatable features at clinical magnetic fields (1.5T and 3T). To the best of our knowledge, cerebral perfusion MRI has not been reported in sheep.…”
Section: Introductionmentioning
confidence: 99%